Penegakan Kedaulatan Di Wilayah Udara Indonesia Berdasarkan Undang-Undang Nomor 1 Tahun 2009 Tentang Penerbangan - Salrik Roland Saily; Johanis Steny Franco Peilouw; Irma Halima Hanafi (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This study discusses the enforcement of sovereignty in Indonesian airspace based on Law number 1 of 2009 concerning Avitiation. Purposes of the Research: Rieviewing and discusses froms the regulation and law enforcement in air space in Indonesian airspace based on Law number 1 of 2009 concering Aviation. Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach.Results of the Research: The resukts of this study indicate that violations of airspace in Indonesian are still common considering thaht Indonesian has a fairly large area and is limited by violation detection radar devices so that it is very vulnerable in Indonesia’s airspace to be entered by foreign civilian aircraft. Indonesian has not only happened repeatedly until the beginning of 2019, but in government regulation number 4 of 2018 concering security of the airspace of the republic of Indonesia, it has been explained and emphasized regarding securing airspace in indonesian airspace in article 1 paragraph (8) government regulations.